ANALISIS GAYA MENGAJAR GURU DI SEKOLAH DASAR - Nur Hasanah, Fatimah; Aulia Rahman, Maulida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the importance of elementary school teachers' teaching styles in supporting the learning process in elementary schools. In practice, there are still many variations in teacher teaching styles that have an impact on the effectiveness of classroom learning. This study aims to analyze the teaching styles used by teachers in the learning process, especially in elementary schools. This study uses a quantitative approach with a descriptive survey method. The population of this study were all teachers at SDN 1 Sindanggalih and SDN 6 Sindanggalih with a total sampling technique of 16 teachers. Data collection was carried out using a questionnaire based on teaching style indicators which include voice variation, attention concentration, silence, eye contact, body movements, and changes in teacher position. The results of the validity test showed 16 valid items and the reliability test obtained a Cronbach's Alpha value of 0.824 which indicates high reliability. Data analysis used descriptive statistics with the help of SPSS. The results of the study show that teachers have different and diverse teaching styles with a tendency towards interactive and communicative styles, although there is still the use of teacher-centered styles. These findings indicate the importance of implementing a variety of effective teaching styles to increase student engagement and learning effectiveness in elementary schools.